2013
DOI: 10.1038/jcbfm.2013.70
|View full text |Cite
|
Sign up to set email alerts
|

Combined Antiapoptotic and Antioxidant Approach to Acute Neuroprotection for Stroke in Hypertensive Rats

Abstract: We hypothesized that targeting key points in the ischemic cascade with combined neuroglobin (Ngb) overexpression and c-jun N-terminal kinase (JNK) inhibition (SP600125) would offer greater neuroprotection than single treatment after in vitro hypoxia/ reoxygenation and in a randomized, blinded in vivo experimental stroke study using a clinically relevant rat strain. Male spontaneously hypertensive stroke-prone rats underwent transient middle cerebral artery occlusion (tMCAO) and were divided into the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
(76 reference statements)
1
17
0
Order By: Relevance
“…In another line of therapy, a CAV-2 vector expressing neuroglobin, in combination with a c-Jun N-terminal kinase inhibitor, protects against oxidative stress and neuronal apoptosis induced by stroke in hypertensive rats [50]. In this study a direct comparison of CAV-2 vector biodistribution in the rat brain also showed that CAV-2 vectors significantly outperform HIV-1 vectors.…”
Section: Cav-2 Vectors To Understand and Treat Neurodegenerative Disementioning
confidence: 91%
“…In another line of therapy, a CAV-2 vector expressing neuroglobin, in combination with a c-Jun N-terminal kinase inhibitor, protects against oxidative stress and neuronal apoptosis induced by stroke in hypertensive rats [50]. In this study a direct comparison of CAV-2 vector biodistribution in the rat brain also showed that CAV-2 vectors significantly outperform HIV-1 vectors.…”
Section: Cav-2 Vectors To Understand and Treat Neurodegenerative Disementioning
confidence: 91%
“…Excitotoxicity, inflammation, oxidative stress, necrosis, and apoptosis have been identified as key contributory pathways underlying lesion progression after ischemia. 4 Dissolving the clot allows the restoration of normal blood flow to the affected part of the brain. However, reperfusion can also cause tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress induced by reperfusion after CA leads to the exhaustion of cerebral antioxi- dant reserves and causes severe oxidative damage. Moreover, it has been reported that oxidative stress-induced lipid peroxidation alters the antioxidant defense system and plays an important role in the neurological damage occurring after cerebral ischemia (22,23). Surplus amount of ROS generation is thought to be the key module of neuronal damage in the brain.…”
Section: Discussionmentioning
confidence: 99%